1997
DOI: 10.1074/jbc.272.50.31641
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of the Mouse Aldolase A Gene

Abstract: The expression of aldolase A L-type mRNA is increased in growth-arrested mouse NIH3T3 cells and remarkably down-regulated in actively proliferating cells. Treatment of proliferating cells with cycloheximide abolished the down-regulation of L-type mRNA expression, thus indicating that a protein factor acts as repressor in proliferating cells. Transient transfection experiments in NIH3T3 cells showed that a negative regulatory cis-element (NRE) is involved in the modulation of the transcriptional activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In fact, we found that the repressor complex down-regulates the transcription of the L-type promoter in proliferating cell types, whereas the binding activity of the complex to the DNA is inhibited in growth-arrested cells, and this correlates with an increased L-type gene transcription (29,30).…”
Section: Prmt5 Knockdown Enhances L-type Aldolase a Mrna Expression-bmentioning
confidence: 90%
See 2 more Smart Citations
“…In fact, we found that the repressor complex down-regulates the transcription of the L-type promoter in proliferating cell types, whereas the binding activity of the complex to the DNA is inhibited in growth-arrested cells, and this correlates with an increased L-type gene transcription (29,30).…”
Section: Prmt5 Knockdown Enhances L-type Aldolase a Mrna Expression-bmentioning
confidence: 90%
“…This prompted us to verify the recruitment of PRMT5 to the promoter regions of genes encoding proteins involved in cell cycle regulation using the cell cycle-dependent modulation of L-type aldolase A promoter activity as an experimental tool (29,30). Our findings indicate that PRMT5 is involved in the formation of the complex that negatively regulates aldolase A gene transcription during the cell cycle (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear protein extracts from NIH 3T3 and Caco‐2 cells were prepared according to Dignam et al [16] modified as previously described [11]. Southwestern experiments [11] and EMSA [1] were performed as described.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear protein extracts from NIH 3T3 and Caco‐2 cells were prepared according to Dignam et al [16] modified as previously described [11]. Southwestern experiments [11] and EMSA [1] were performed as described. In phosphatase assay nuclear extracts (4 μg) were incubated with or without potato acid phosphatase (PAP) 0.06 and 0.12 U. for 20 min at 37°C in Parker buffer 1× (glycerol 10%, HEPES 10 mM (pH 7.9), KCl 100 mM, EDTA 0.1 mM, DTT 0.25 mM) prior to the EMSA experiments.…”
Section: Methodsmentioning
confidence: 99%